STUDI PERTAMBAHAN PANJANG SULUR LIANA BERDAU LEBAR (Merremia peltata) DI AREAL KAMPUS POLITEKNIK PERTANIAN NEGERI SAMARINDA - M. Fadjeri; Emi Malaysia; Dwinita Aquastini (JURNAL AGRIMENT, 2021)
The purpose of this research is to find out the increase in the length of long Liana Broad-leavedtendrils ( Merremia Peltata) in the Area of Samarinda State Agricultural Polytechnic Campus. Theresearch was conducted for 2 months in the area Campus of Agricultural Polytechnic StateSamarinda which includes preparation and marking activities of selected liana, making ajir, wrappingliana to stick where to vine, data retrieval, data processing and reporting. The data taken in this studyare: (1) Increase in the length of tendrils Liana Broad-leaved ( Merremia Peltata) that is deliberatelyallowed to creep above the surface of the ground (treatment 1st); (2) increase in the length of tendrilsLiana Broad-leaved ( Merremia Peltata) deliberately bought on stick where to vine (treatment 2nd);dan (3) the number of Liana twists on each stick where to vine.Sampling is done intentionally(purposive sampling), namely by searching for liana in campus areas that are eligible for use inresearch. The number of samples for lyanas that are deliberately left to creep above ground level anddeliberately wrapped around stick where to vine each 30 individuals. The results of the study are asfollows: (1) the increase in the length of tendrils Liana Broad-leaved (Merremia Peltata) that isdeliberately allowed to creep above the ground (treatment 1st) is the amount of increase in tendrillength 12945.10 cm and average 431.50 cm / 6 weeks;(2) increase in the length of tendrils LianaBroad-leaved ( Merremia Peltata) deliberately bought on ajir (treatment 2) is the amount of increase intendril length 12835.10 cm and average 427.84 cm / 6 weeks; and (3) the increase of Liana BroadLeaved (Merremia Peltata) in stick where to vine is the amount of 214.00 twists and an average of7.13 twists.